Relationships between menopausal syndrome and sleeping of middle-aged women - Park, Yi Kyun (J Phys Ther Sci, 2015)
[Purpose] This study aimed to examine the correlation between menopausal syndrome and sleep state of middle-aged women, and to examine the factors influencing menopausal syndrome. [Subjects] The subjects included 59 middle-aged women in Seoul, South Korea. [Methods] A cross-sectional design was adopted. The measurement tools were a general characteristics form, Menopause Symptom Index (MENSI), and sleep state scale. [Results] There was a significantly negative correlation between menopausal syndrome and sleep state of middle-aged women. The analyses showed that the prediction model was significant. The value of the adjusted R(2) was 0.279, which corresponds to an explanatory power of 27.9%. The factor found to have the most influence on menopausal syndrome of middle-aged women was sleep state, followed by sexual life satisfaction, and health status. [Conclusion] Nursing intervention programs for alleviating menopausal syndrome of middle-aged women are essential in order to improve sleep state, sexual life satisfaction, and health status. The findings from this study will contribute to help them for controlling and relieving the menopausal syndrome of middle-aged women.